Research on the Status of KAP and Countermeasures of the Scientific Research Level of TCM Rehabilitation Practitioners - Jian SONG; Zhizhen LIU; Jingsong WU; Juan PENG; Bin CHEN; Jia HUANG (康复学报)
Objective:To analyze the status and problems of"knowledge-attitude-practice" (KAP) for rehabilitation practitioners of TCM in different classes of rehabilitation medical institutions, and to propose corresponding countermeasures.Methods:TCM rehabilitation practitioners in 34 provinces, municipalities and autonomous regions were selected as respondents. The questionnaires on the KAP of scientific research level in TCM rehabilitation practitioners were voluntarily responded to the samples. The samples were divided into tertiary hospital group and non-tertiary hospital group according to the hospital level, and compare the status of KAP between two groups.Results:We received a total of 494 valid questionnaires, the efficiency of the questionnaire was 81.79%, with 369 cases in the tertiary hospital group and 125 cases in the non-tertiary hospital group. At the knowledge dimension, compare with non-tertiary hospital group, the ability of database literature retrieval, rehabilitation research and design of the tertiary hospital group were higher (P<0.05), while there were no significant differences in rehabilitation literature reading and statistical analysis of scientific research (P>0.05). At the attitude dimension, the difficulties in the scientific research process of tertiary hospitals were significantly lower than those in non-tertiary hospital groups (P<0.05), and there were no significant differences in importance recognition of the scientific research, reasons for scientific research, solutions when encounter difficulties (P>0.05). At the practice dimension, the time spent in scientific research, the opportunity to participate in high-level research projects, and the number of domestic journal paper output were significantly higher than those in non-tertiary hospital groups (P<0.05), and there were no significant differences in adjustment of scientific research plan, the opportunity to undertake high-level subjects, the number of papers in SCI source journal, and the number of scientific research-related training participations (P>0.05). In addition, the results of canonical correlation analysis showed that practice dimension was positive correlation to hospital classification, knowledge dimension and attitude dimension, the higher the knowledge and attitude dimensions, the greater the influence on the practice dimensions.Conclusion:There were uneven distribution of talents and uneven level of scientific research in different class of rehabilitation medical institutions. The overall scientific research capabilities of TCM rehabilitation practitioners in non-tertiary hospitals is weak, while tertiary hospitals have not been given full play to the corresponding advantages of scientific research and talents. Therefore, it is necessary to strengthen the knowledge acquisition, attitude support and practical application of scientific research, to cultivate high level clinical and scientific research talents of rehabilitation of TCM, and promote the subject development of rehabilitation in TCM.